The Development of Kefir Milk Student Worksheets Based on Free Inquiry on Biotechnology Course - Milla Listiawati; Nopy Melina (Universitas Wiralodra, 2020)
The background of this research is that there are still errors in the practice of making milk kefir in the biotechnology practice guide. Therefore, it is necessary to develop a free inquiry-based kefir worksheet that can be used by prospective teacher students in biotechnology courses. The method used is the research and development method which consists of define, design, and develop stages. Data collection techniques using the method of observation and questionnaires. The subjects of this study were the sixth semester biology education students. The results showed the validity of the questionnaire items had a score of 0.65 with the category of